Enhancement in Human Insulin Precursor Secretion by Pichia pastoris through Modification of Expression Conditions - Dini Nurdiani; Hariyatun Hariyatun; Nuruliawaty Utami; Eko Wahyu Putro; Wien Kusharyoto (HAYATI Journal of Biosciences, 2022)
Pichia pastoris is an alternative yeast expression system to produce heterologous proteins. It has excellent characteristics for an industrial cell factory, such as its ability to reach high cell densities, high secretory capacity, and a low level of native proteins. In our previous study, we introduced a synthetic insulin precursor (IP)-encoding gene constructed in a pD902 expression vector into P. pastoris. However, the P. pastoris recombinant strains expressed a little amount of IP protein. Here, we modified the expression conditions, including inoculum density, methanol concentration, methanol induction time, pH, and temperature, to obtain a higher amount of secreted IP than our previous result. Protein analysis for studying the five parameters was conducted by SDS-PAGE, and the protein amount was estimated by ImageJ applying lysozyme as standard. We successfully enhanced the IP expression by modifying expression conditions. The highest increased of up to 100 folds was achieved when methanol concentration for induction was arranged at 3% (v/v), and the initial cell density for methanol induction was set at an optical density at 600 nm (OD600) of approximately 10 compared to the standard procedure, where the expression was set at 0.5% (v/v) methanol induction and initial cell density at OD600 = 1.